2003
DOI: 10.1023/a:1026110417294
|View full text |Cite
|
Sign up to set email alerts
|

Tissue and Serum MUC1 Mucin Detection in Breast Cancer Patients

Abstract: Tumor MUC1 expression as well as levels of MUC1, MUC1 circulating immune complexes (MUC1-CIC) and free antibodies against MUC1 (IgG and IgM-MUC1) were evaluated in 70 breast cancer patients with different stages of disease. Controls included: 135 serum samples from healthy women, normal mammary tissue samples (n = 7) and benign breast disease specimens (n = 6). In all assays, pre- and post-vaccination serum samples from breast cancer patients belonging to a vaccination protocol developed at the Memorial Sloan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 38 publications
4
45
1
1
Order By: Relevance
“…As for circulating anti-MUC1 IgM, stage II, III, and IV patients had slightly increased levels compared to stage I patients, an observation also noted in an earlier study (4). Therefore, there are many similarities in the changes of circulating anti-MUC1 antibodies at different stages of breast cancer before and after primary treatment, which implies these changes are related to the stages of the disease but not to the primary treatment.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…As for circulating anti-MUC1 IgM, stage II, III, and IV patients had slightly increased levels compared to stage I patients, an observation also noted in an earlier study (4). Therefore, there are many similarities in the changes of circulating anti-MUC1 antibodies at different stages of breast cancer before and after primary treatment, which implies these changes are related to the stages of the disease but not to the primary treatment.…”
Section: Discussionsupporting
confidence: 70%
“…A negative correlation between circulating anti-MUC1 antibodies and MUC1 antigen has been found in patients with some malignant tumors (4,20,23). In the present study, we found a significantly negative correlation between the CA15-3 (MUC1 antigen) serum level and that of the anti-MUC1 IgG antibody in patients with an advanced stage of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shin et al [78] reported QD based probe (emission maxima at 565 nm) covalently conjugated to MUC-1 aptamer. BOBO-3 that demonstrates significant fluorescence enhancement when intercalated into folded regions of aptamer with double helix structure was used to stain the duplex regions, resulting in the assembly of QD-aptamer conjugates over-loaded with BOBO-3 molecules.…”
Section: Cancer Cell Imaging By Aptamer-conjugated Qdsmentioning
confidence: 99%
“…Studies investigating the role of tumor-associated antigens (TAAs) in cancer diagnosis and progression have focused on the MUC1 antigen, which is overexpressed in most solid epithelial and non-solid hematological tumors including multiple myeloma (1)(2)(3). Soluble MUC1 (sMUC1) levels were reported to be elevated in sera of patients with solid tumors such as breast carcinoma, and non-solid tumors such as multiple myeloma, using FDA approved sMUC1 assays CA15.3 and CA27.29 directed to the extracellular tandem repeat array (TRA) domain (3,4).…”
Section: Introductionmentioning
confidence: 99%